KETIMPANGAN SOSIAL DAN MORALITAS DALAM NOVEL ORANG-ORANG PROYEK KARYA AHMAD TOHARI KAJIAN SOSIOLOGI SASTRA - Mulyadi; Irna Fitriana; Idris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of social inequality in the novel Orang-Orang Proyek by Ahmad Tohari through a sociological approach to literature. The method used is qualitative with a descriptive-analytical design. The primary data consist of the novel text, while secondary data are derived from various supporting references such as books, journals, and scholarly articles. Data collection is conducted through a reading and note-taking technique, while data analysis employs content analysis with the researcher as the main instrument. The validity of the data is ensured through theoretical triangulation.2The results of the study indicate that social inequality in the novel is manifested in several main forms. First, there is inequality in access to power, where the project elites have full dominance in decision-making, while workers occupy subordinate positions. Second, economic inequality is reflected in the unequal distribution of capital and welfare between project authorities and laborers who face limited living conditions. Third, inequality in education and life opportunities is evident in the limited access of lower-class groups to self-improvement and social mobility. Fourth, there is unequal control over information and opportunities for political participation, which further strengthens the dominant position of the elites. In addition, structural domination is also reflected in practices that restrict the participation of lower-class communities in the development process.Thus, the novel represents social inequality as a complex structural phenomenon involving unequal relations of power, economic resources, and social access, while also illustrating how development actually widens the gap between elite groups and the lower classes.